Effectiveness of «Universal Newborn Hearing Screening program» of Caja Costarricense del Seguro Social, in detecting deafness in children, from 2016 to 2018 - González, Leiner Rodríguez; Zeledón Díaz, Ana Laura; Mora, Óscar Centeno (Población y Salud en Mesoamérica, 2021)
Introduction: Hearing screening is a detection method, its objective is to provide an early intervention that allows reducing the negative consequences of an eventual hearing impairment, in the integral development of the infant. Costa Rica has implemented a universal neonatal hearing screening program in the public health system, where the hearing of every child born in the country is examined before the first month of life. Although multiple benefits have been perceived, it is important to demonstrate with scientific evidence if it accomplishes its objectives. Methodology: the effectiveness of the Universal Newborn Hearing Screening Program in Costa Rica was analyzed, based on the information recorded from 37,656 children evaluated since 2016 to 2018, through empirical contrast using both descriptive techniques: frequency distribution of variables, as well as the use of inferential tests: chi square and analysis of variance (ANOVA). Results: 71 % of the sample was between 0 and 3 days old at the moment of being examined. Its performance over time and extension to different health centers has been satisfactory, likewise, the number of infants evaluated has been up to 98 % of the population. Conclusions: the TANU program is effective in most of the aspects analyzed, the identification of risk factors and the early detection of hearing disorders are outstanding, however, improvements are proposed in relation to the handling of information.